The Relationship Between Customer Satisfaction and Organizational Success: A Study of Panasonic - Wanneyda Suvanmanee; Daisy Mui Hung Kee; Zhi Wei Lee; Chia Miin Low; Muhamad Amir Zakwan; Ankit Gupta; Rudresh Pandey; Fay Fahad Alfahad; Majdi Anwar Quttainah (AIBPM Publisher, 2020)
The purpose of this study is to examine the customers' satisfaction that drives to the success of the company. There is a high competition between the brand of the electrical appliance, therefore customer satisfaction is one of the key elements to the success of the company. The study used a quantitative method which is a questionnaire to collect the data from respondents. It will enhance the understanding and importance of customer satisfaction toward a company able to lead to company success. The findings indicated that customer satisfaction is an important prediction of the success of the company.